Gust Response Analysis for Helicopter Rotors in the Hover and Forward Flights - Linpeng Wang; Yuting Dai; Chao Yang (Shock and Vibration)
Dynamic load due to gust for helicopter rotors directly affects the structural stress and flight performance. In case of gust, it may cause the loss of trust force or the increase of deflection for rotors. In current work, an effective coupled aeroelastic model based on a medium-deflection beam theory and a nonlinear unsteady aerodynamic model in the time domain were constructed. Three types of gust in vertical direction were added in the model. The dynamic response and structural load for helicopter rotors under three types of gust were calculated, respectively. Results indicated that when rotors suffer a gust in hover at downward direction, the thrust force on rotor disk would decrease significantly when the gust amplitude increases, which should be paid attention in the design. Among the three gust types with the same gust strength, the maximum instantaneous shear force due to impulse shape gust is the largest. When the rotors suffer a gust in a forward flight, the shear force at the root of rotors would increase with the gust strength first but then it decreases. More attention should be paid to the decrease of thrust force and the increase of structural load in a forward flight.